ATTITUDE OF STUDENTS IN READING COMPREHENSION - Muchtar Naely (Institut Agama Islam Negeri Palopo, 2015)
Reading is certainly one area that receives considerable attention in academic life. Teacher/lecturer have come to realize that students attitude toward reading is every bit as important as improving students reading comprehension. The creation and maintenance of positive attitude toward reading comprehension is expected to be steppingstone of the students success of being good reader. This paper is discussed about the importance of attitudes in relation with reading comprehension. It is expected will give contribution for educator in teaching reading comprehension in all level of education.